Arterial elasticity in obese adolescents with clinical features of insulin resistance. (January 2015) - Ho, Mandy; Benitez-Aguirre, Paul Z; Donaghue, Kim C; Mitchell, Paul; Baur, Louise A; Jenkins, Alicia J; Craig, Maria E; Cowell, Chris T; Garnett, Sarah P
Objective: To determine whether arterial elasticity differs between obese adolescents with clinical insulin resistance (IR), type 1 diabetes (T1D) and healthy non-obese controls. Methods: This cross-sectional study evaluated 69 adolescents with clinical IR, 91 with T1D and 63 age-matched (10- to 18-year-old) controls. Arterial elasticity was measured using radial tonometry pulse-wave analysis. Stepwise multiple regression analyses were performed to assess the determinants of the small and large arterial elasticity indices (SAEI and LAEI). Results: SAEI and LAEI raw values were higher in the IR group than the controls, and these did not differ between the T1D and control groups. Weight and diastolic blood pressure (DBP) were significant predictors of SAEI. After adjustment for weight and DBP, SAEI decreased by 0.65 mL/mmHg × 100 for each 1-year increase in age in the IR group. SAEI was not different across the groups after controlling for weight and DBP. Height was the strongest predictor of LAEI which remained higher in the IR group after controlling for height and blood pressure. Conclusion: Obese adolescents with clinical IR have a higher SAEI, which declines with age; this may reflect a pathway to an increased risk of premature cardiovascular disease.